High-adhesion diamond-like film coating method
By depositing a titanium base layer and a titanium carbide and chromium deposition layer on the alloy substrate, and forming a diamond-like layer with anode ion beam technology, solving the problem of internal stress increase caused by the increase in the thickness of the diamond-like film, and achieving high adhesion, low stress and high hardness coating.
Patent Information
- Application Number
- CN202510119804.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, when the thickness of the diamond-like film increases, it is easy to increase the internal stress, lead to peeling from the alloy substrate and increasing the roughness of the coating surface, and the friction coefficient will also increase, making it difficult to achieve high-thickness and low-stress coating.
Titanium is used as the base layer, and the bottom layer and the deposition layer are deposited by magnetron sputtering technology, and then a pre-deposition diamond-like layer is formed in the vacuum cavity using anode ion beam technology, and a diamond-like layer is formed under the graphite cathode target to control internal stress and hardness.
It effectively reduces the internal stress of diamond-like film, improves the adhesion and wear resistance of the coating, significantly improves the hardness, extends the service life, and maintains a low coefficient of friction.
Smart Images

Figure CN119553225A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy surface coating, and in particular to a high-adhesion diamond-like film coating method. Background Art
[0002] With the upgrading of modern manufacturing industry and the dual pressure of resources and environment, alloy substrates are sometimes limited by their own defects of low hardness and poor wear resistance and cannot fully meet the needs.
[0003] Alloy surfaces are often plated to form a dense coating, which has good wear resistance, conductivity and decorative properties. Diamond-like carbon film is a metastable amorphous carbon film containing a large number of sp3 bonds. Carbon atoms are mainly bonded by sp3 and sp2 hybrid bonds. Its performance is close to that of diamond. Due to its high hardness and high elastic modulus, it is very suitable as a wear-resistant coating and is widely used in alloy surface treatment.
[0004] At present, the thicker the diamond-like carbon film is, the higher its wear resistance and hardness will be, but it is very easy to cause the internal stress of the diamond-like carbon to increase, which not only easily causes it to peel off from the alloy substrate, but also increases the roughness of the coating surface and the friction coefficient.
[0005] Therefore, it is urgent to provide a method for coating diamond-like carbon thin films that is simple and convenient to operate, has good wear reduction effect, and can achieve low stress and high thickness. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a high-adhesion diamond-like film coating method.
[0007] A high-adhesion diamond-like carbon thin film coating method comprises the following steps: S1. Ultrasonic cleaning and drying of the alloy substrate, heat preservation at 160-200° C. for 1-2 h under vacuum, and plasma cleaning for 10-30 min under argon protection to obtain a pretreated alloy; S2, using titanium as a target, magnetron sputtering a bottom layer onto the surface of the pretreated alloy, and then using titanium carbide and chromium as targets, magnetron sputtering a deposited layer on the surface of the bottom layer at the same time; S3. Maintain the vacuum degree in the vacuum chamber at 0.2-0.6Pa, introduce acetylene gas into it, and use anode ion beam technology to form a pre-deposited diamond-like carbon layer on the surface of the deposited layer; then place it in a filtered cathode vacuum arc device, with the cathode target material being graphite, and form a diamond-like carbon layer under the conditions of gas pressure of 0.2-0.6Pa, current of 50-70A, and vacuum negative bias of 60-100V.
[0008] Preferably, in S1, the alloy substrate is ultrasonically cleaned using deionized water, acetone, and anhydrous ethanol in sequence.
[0009] Preferably, in S2, the thickness of the bottom layer is 0.1-1 mm.
[0010] Preferably, in S2, the thickness of the deposited layer is 1-3 mm.
[0011] Preferably, in S2, the power ratio of the titanium carbide target to the chromium target is 1-2:1.
[0012] Preferably, in S3, the flow rate of acetylene gas is 50-150 sccm.
[0013] Preferably, in S3, the thickness of the pre-deposited diamond-like carbon layer is 5-10 μm.
[0014] Preferably, in S3, during the treatment using anode ion beam technology, the ion beam source is 1200-2000V, the bias power supply is 1500-2200V, and the duty cycle is 30-45%.
[0015] Preferably, in S3, the thickness of the diamond-like carbon layer is 10-50 μm. Beneficial effects:
[0016] The present invention adopts titanium as the bottom layer, which can effectively alleviate the difference in thermal expansion coefficient between the alloy bottom material and the diamond-like carbon layer, and uses titanium carbide and chromium as target materials to effectively reduce internal stress, effectively inhibit crack propagation, and improve the stability of the diamond-like carbon film.
[0017] The present invention sequentially sputters a base layer and a deposited layer on the alloy surface, and then uses an anode ion beam technology to form a pre-deposited diamond-like layer, which can effectively enhance the adhesion between the coating and the substrate, and at the same time improve the adhesion and wear resistance of the subsequent sputtered diamond-like film, and has high adhesion strength, significantly improved hardness, and effectively extended service life.
[0018] The present invention forms a pre-deposited diamond-like layer by using an anodic ion beam technique, and then forms a diamond-like layer using graphite as a cathode target material. On the basis of increasing the film thickness, the internal stress is small, and the hardness is high, thereby effectively achieving high hardness and low internal stress of the film layer. The present invention is cleverly designed, and can not only increase the thickness of the diamond-like layer, but also effectively buffer the huge stress carried by the thick diamond-like layer, and can improve the bonding force with the substrate, thereby ensuring that the product has a low friction coefficient.
[0019] The process of the invention has high stability, is pollution-free, green and environmentally friendly, and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a comparison chart of the hardness and residual stress of the coatings obtained in Example 5 and Comparative Examples 1-2.
[0021] Figure 2 This is a comparison chart of the critical load for complete peeling of the coating and the scratch crack propagation resistance of the coatings obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0022] The present invention will be further explained below in conjunction with specific embodiments.
[0023] The aluminum alloy used below is obtained by T6 heat treatment of 6061 series aluminum alloy. Example 1
[0024] A high-adhesion diamond-like carbon thin film coating method comprises the following steps: S1. The aluminum alloy is ultrasonically cleaned with deionized water, acetone, and anhydrous ethanol in sequence, placed in an oven for drying, placed in a vacuum chamber, evacuated, kept at 160° C. for 1 hour, and plasma cleaned for 10 minutes under argon protection to obtain a pretreated aluminum alloy; S2. Using titanium as the target, magnetron sputtering the bottom layer onto the pretreated aluminum alloy surface, the thickness of the bottom layer is 0.1 mm, and using TiC and chromium as the target, magnetron sputtering the deposition layer on the bottom layer surface, the thickness of the deposition layer is 1 mm, wherein the power ratio of the TiC target to the chromium target is 1:1; S3. Maintain the vacuum degree in the vacuum chamber at 0.2Pa, introduce acetylene gas at a flow rate of 50sccm, and use anode ion beam technology to form a pre-deposited diamond-like carbon layer with a thickness of 5μm on the surface of the deposited layer, wherein the ion beam source is 1200V, the bias power supply is 1500V, and the duty cycle is 30%; then place it in a filtered cathode vacuum arc device, with the cathode target material being graphite, and under the conditions of a gas pressure of 0.2Pa, a current of 50A, and a vacuum negative bias of 60V, a diamond-like carbon layer with a thickness of 10μm is formed. Example 2
[0025] A high-adhesion diamond-like carbon thin film coating method comprises the following steps: S1. The aluminum alloy is ultrasonically cleaned with deionized water, acetone, and anhydrous ethanol in sequence, placed in an oven for drying, placed in a vacuum chamber, evacuated, kept at 200° C. for 2 h, and plasma cleaned for 30 min under argon protection to obtain a pretreated aluminum alloy; S2. Using titanium as the target, magnetron sputtering the bottom layer onto the pretreated aluminum alloy surface, the thickness of the bottom layer is 1 mm, and using TiC and chromium as the target, magnetron sputtering the deposition layer on the bottom layer surface, the thickness of the deposition layer is 3 mm, wherein the power ratio of the TiC target to the chromium target is 2:1; S3. Maintain the vacuum degree in the vacuum chamber at 0.6Pa, introduce acetylene gas at a flow rate of 150sccm, and use anode ion beam technology to form a pre-deposited diamond-like carbon layer with a thickness of 10μm on the surface of the deposited layer, wherein the ion beam source is 2000V, the bias power supply is 2200V, and the duty cycle is 45%; then place it in a filtered cathode vacuum arc device, with the cathode target material being graphite, and under the conditions of a gas pressure of 0.6Pa, a current of 70A, and a vacuum negative bias of 100V, a diamond-like carbon layer with a thickness of 50μm is formed. Example 3
[0026] A high-adhesion diamond-like carbon thin film coating method comprises the following steps: S1. The aluminum alloy is ultrasonically cleaned with deionized water, acetone, and anhydrous ethanol in sequence, placed in an oven for drying, placed in a vacuum chamber, evacuated, kept at 170° C. for 100 min, and plasma cleaned under argon protection for 15 min to obtain a pretreated aluminum alloy; S2. Using titanium as the target, magnetron sputtering the bottom layer onto the pretreated aluminum alloy surface, the bottom layer thickness is 0.7 mm, and using TiC and chromium as the target, magnetron sputtering deposition layer on the bottom layer surface, the deposition layer thickness is 1.5 mm, wherein the power ratio of the TiC target to the chromium target is 1.8:1; S3. Maintain the vacuum degree in the vacuum chamber at 0.3Pa, introduce acetylene gas at a flow rate of 120sccm, and use anode ion beam technology to form a pre-deposited diamond-like carbon layer with a thickness of 7μm on the surface of the deposited layer, wherein the ion beam source is 1800V, the bias power supply is 1600V, and the duty cycle is 40%; then place it in a filtered cathode vacuum arc device, with the cathode target material being graphite, and under the conditions of a gas pressure of 0.3Pa, a current of 65A, and a vacuum negative bias of 70V, a diamond-like carbon layer with a thickness of 40μm is formed. Example 4
[0027] A high-adhesion diamond-like carbon thin film coating method comprises the following steps: S1. The aluminum alloy is ultrasonically cleaned with deionized water, acetone, and anhydrous ethanol in sequence, placed in an oven for drying, placed in a vacuum chamber, evacuated, kept at 190° C. for 80 min, and plasma cleaned under argon protection for 25 min to obtain a pretreated aluminum alloy; S2. Using titanium as the target, magnetron sputtering the bottom layer onto the pretreated aluminum alloy surface, the bottom layer thickness is 0.3 mm, and using TiC and chromium as the target materials, magnetron sputtering the deposited layer on the bottom layer surface, the deposited layer thickness is 2 mm, wherein the power ratio of the TiC target material to the chromium target material is 1.2:1; S3. Maintain the vacuum degree in the vacuum chamber at 0.5Pa, introduce acetylene gas at a flow rate of 80sccm, and use anode ion beam technology to form a pre-deposited diamond-like carbon layer with a thickness of 9μm on the surface of the deposited layer, wherein the ion beam source is 1400V, the bias power supply is 2000V, and the duty cycle is 35%; then place it in a filtered cathode vacuum arc device, with the cathode target material being graphite, and under the conditions of a gas pressure of 0.5Pa, a current of 55A, and a vacuum negative bias of 90V, a diamond-like carbon layer with a thickness of 20μm is formed. Example 5
[0028] A high-adhesion diamond-like carbon thin film coating method comprises the following steps: S1. The aluminum alloy is ultrasonically cleaned with deionized water, acetone, and anhydrous ethanol in sequence, placed in an oven for drying, placed in a vacuum chamber, evacuated, kept at 180° C. for 90 min, and plasma cleaned under argon protection for 20 min to obtain a pretreated aluminum alloy; S2. Using titanium as the target, magnetron sputtering the bottom layer onto the surface of the pretreated aluminum alloy, the thickness of the bottom layer is 0.5 mm, and using TiC and chromium as the target, magnetron sputtering the deposition layer on the surface of the bottom layer, the thickness of the deposition layer is 2.5 mm, wherein the power ratio of the TiC target to the chromium target is 1.5:1; S3. Maintain the vacuum degree in the vacuum chamber at 0.4Pa, introduce acetylene gas at a flow rate of 100sccm, and use anode ion beam technology to form a pre-deposited diamond-like carbon layer with a thickness of 8μm on the surface of the deposited layer, wherein the ion beam source is 1600V, the bias power supply is 1800V, and the duty cycle is 38%; then place it in a filtered cathode vacuum arc device, with the cathode target material being graphite, and under the conditions of a gas pressure of 0.4Pa, a current of 60A, and a vacuum negative bias of 80V, a diamond-like carbon layer with a thickness of 30μm is formed.
[0029] Comparative Example 1 A high-adhesion diamond-like carbon thin film coating method comprises the following steps: S1. The aluminum alloy is ultrasonically cleaned with deionized water, acetone, and anhydrous ethanol in sequence, placed in an oven for drying, placed in a vacuum chamber, evacuated, kept at 180° C. for 90 min, and plasma cleaned under argon protection for 20 min to obtain a pretreated aluminum alloy; S2. Using titanium as a target, magnetron sputtering a bottom layer onto the surface of the pretreated aluminum alloy, the thickness of the bottom layer is 0.5 mm; using TiC as a target, magnetron sputtering a deposition layer a onto the surface of the bottom layer, the thickness of the deposition layer a is 1.5 mm; then using chromium as a target, magnetron sputtering a deposition layer b onto the surface of the deposition layer a, the thickness of the deposition layer b is 1 mm; S3. Maintain the vacuum degree in the vacuum chamber at 0.4Pa, introduce acetylene gas at a flow rate of 100sccm, and use anode ion beam technology to form a pre-deposited diamond-like carbon layer with a thickness of 8μm on the surface of the deposited layer, wherein the ion beam source is 1600V, the bias power supply is 1800V, and the duty cycle is 38%; then place it in a filtered cathode vacuum arc device, with the cathode target material being graphite, and under the conditions of a gas pressure of 0.4Pa, a current of 60A, and a vacuum negative bias of 80V, a diamond-like carbon layer with a thickness of 30μm is formed.
[0030] Comparative Example 2 A high-adhesion diamond-like carbon thin film coating method comprises the following steps: S1. The aluminum alloy is ultrasonically cleaned with deionized water, acetone, and anhydrous ethanol in sequence, placed in an oven for drying, placed in a vacuum chamber, evacuated, kept at 180° C. for 90 min, and plasma cleaned under argon protection for 20 min to obtain a pretreated aluminum alloy; S2. Using titanium as the target, magnetron sputtering the bottom layer onto the surface of the pretreated aluminum alloy, the thickness of the bottom layer is 0.5 mm, and using TiC and chromium as the target, magnetron sputtering the deposition layer on the surface of the bottom layer, the thickness of the deposition layer is 2.5 mm, wherein the power ratio of the TiC target to the chromium target is 1.5:1; S3. Place the device in a filtered cathode vacuum arc device, with the cathode target being graphite. Under the conditions of a gas pressure of 0.4 Pa, a current of 60 A, and a vacuum negative bias of 80 V, a diamond-like carbon layer with a thickness of 38 μm is formed on the surface of the deposited layer.
[0031] A nanoindenter was used to measure the hardness of the coatings obtained in Example 5 and Comparative Examples 1-2; and a residual stress meter was used to measure the residual stress of each group of coatings after deposition. A laser emitter and a PDS detector were used to move the sample to change the laser reflection angle to measure and calculate the residual stress value of the film. The stress test range was 0.001-100 GPa, and the resolution was 0.001 GPa.
[0032] like Figure 1 As shown, the coating obtained in Example 5 has the highest hardness and the lowest residual stress, which is better than that of Comparative Examples 1-2 (P < 0.05).
[0033] The friction properties of the coatings obtained in Example 5 and Comparative Examples 1-2 were measured using a multifunctional high-temperature friction and wear testing machine. A certain normal load was applied to the grinding pair to make it reciprocate on the sample surface. The scratch tracks were observed under a microscope. It was found that during the sliding of the indenter, edge cracks, conformal cracks, local peeling and complete peeling would appear on the surface of each group of coatings in turn.
[0034] The critical load when microcracks appear in the coating is defined as Lc1, the critical load when the coating begins to peel off is defined as Lc2, and the critical load when the coating completely peels off is defined as Lc3. This application uses Lc3 to characterize the bonding strength of the coating, and the toughness of the coating is characterized by the scratch crack propagation resistance CPRs.
[0035] CPRs = Lc1 × (Lc2 – Lc1) like Figure 2 As shown, the bonding strength and scratch crack propagation resistance of the coating obtained in Example 5 are the highest, which are better than those of Comparative Examples 1-2 (P < 0.05).
[0036] The applicant believes that this is because the present invention sequentially sputters the base layer and the deposited layer on the surface of the aluminum alloy, and then uses the anode ion beam technology to form a pre-deposited diamond-like layer, which can effectively enhance the adhesion between the coating and the substrate, and at the same time improve the adhesion and abrasion resistance of the subsequent sputtered diamond-like film, and the hardness is significantly improved, effectively extending the service life; at the same time, the present invention forms a pre-deposited diamond-like layer through the anode ion beam technology, and then forms a diamond-like layer with graphite as the cathode target material. On the basis of increasing the film thickness, the internal stress is small and the hardness is high, which effectively achieves high hardness and low internal stress of the film layer.
[0037] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A high-adhesion diamond-like carbon thin film coating method, characterized in that: The steps include: S1. Ultrasonic cleaning and drying of the alloy substrate, heat preservation at 160-200° C. for 1-2 h under vacuum, and plasma cleaning for 10-30 min under argon protection to obtain a pretreated alloy; S2, using titanium as a target, magnetron sputtering a bottom layer onto the surface of the pretreated alloy, and then using titanium carbide and chromium as targets, magnetron sputtering a deposited layer on the surface of the bottom layer at the same time; S3. Maintain the vacuum degree in the vacuum chamber at 0.2-0.6Pa, introduce acetylene gas into it, and use anode ion beam technology to form a pre-deposited diamond-like carbon layer on the surface of the deposited layer; then place it in a filtered cathode vacuum arc device, with the cathode target material being graphite, and form a diamond-like carbon layer under the conditions of gas pressure of 0.2-0.6Pa, current of 50-70A, and vacuum negative bias of 60-100V.
2. The high-adhesion diamond-like carbon thin film coating method according to claim 1, characterized in that: In S1, the alloy substrate is ultrasonically cleaned using deionized water, acetone, and anhydrous ethanol in sequence.
3. The high-adhesion diamond-like carbon thin film coating method according to claim 1, characterized in that: In S2, the bottom layer thickness is 0.1-1 mm.
4. The high-adhesion diamond-like carbon thin film coating method according to claim 1, characterized in that: In S2, the thickness of the deposited layer is 1-3 mm.
5. The high-adhesion diamond-like carbon thin film coating method according to claim 1, characterized in that: In S2, the power ratio of the titanium carbide target to the chromium target is 1-2:
1.
6. The high-adhesion diamond-like carbon thin film coating method according to claim 1, characterized in that: In S3, the flow rate of acetylene gas is 50-150 sccm.
7. The high-adhesion diamond-like carbon thin film coating method according to claim 1, characterized in that: In S3, the thickness of the pre-deposited diamond-like carbon layer is 5-10 μm.
8. The high-adhesion diamond-like carbon thin film coating method according to claim 1, characterized in that: In S3, during the treatment process using anode ion beam technology, the ion beam source is 1200-2000V, the bias power supply is 1500-2200V, and the duty cycle is 30-45%.
9. The high-adhesion diamond-like carbon thin film coating method according to claim 1, characterized in that: In S3, the thickness of the diamond-like carbon layer is 10-50 μm.
Citation Information
Patent Citations
Deposition method of low-stress corrosion-resistant multilayer diamond-like carbon (DLC) film
CN103938211A
Method for depositing amorphous diamond thick film on steel substrate by using multi-energy ion beams
CN105779937A
Thickened composite film based on diamond-like carbon thin film and coating method of thickened composite film
CN107022745A